Reducing antinutrient content in raw jackfruit bulb flour and seed flour through fermentation by Saccharomyces cerevisiae (International Journal of Food and Nutritional Sciences, 2025)
Koozha type jackfruit in their raw stage was selected. Bulbs and seeds were separated andprocessed in to flour. Considering the fact that flatulence interferes with the consumption ofjackfruit, to reduce the level of oligosaccharides, flours were made into batter and subjectedto fermentation with Saccharomyces cerevisiae @ 5g/kg for 6 hrs and 8 hrs and 12 hrsrespectively. Fermentation resulted in proteolytic degradation of proteins into amino acidsand amylolytic breakdown of carbohydrates into sugars and organic acids. Theoligosaccharide (Raffinose) content in treated and pre treated jackfruit bulb flour treated withSaccharomyces cerevisiae at different deviations of fermentation differed in the HPTLCassay. Raffinose content in jackfruit bulb flour was 0.75 µg g-1, 0.63 µg g-1, 0.58 µg g-1and0.74 µg g-1in control (F0), F1, F2, F3 respectively. For jackfruit bulb flour and seed flour 8hour fermentation was found to contain the comparatively less oligosaccharides than othertreatments.